2016
DOI: 10.1590/0102-311x00115614
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Brazilian version of the Hospital Survey on Patient Safety Culture (HSOPSC): a pilot study

Abstract: The evaluation of the culture of patient safety in hospitals is nowadays considered as a management too, since it helps to identify problem areas and provide valuable information for planning improvements. This study explored the reliability and validity of the Brazilian version of the Hospital Survey on Patient Safety Culture, an instrument that evaluates characteristics of patient safety culture among hospital staff. The reliability of the instrument was evaluated by analyzing the internal consistency of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
80
2
50

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(138 citation statements)
references
References 19 publications
6
80
2
50
Order By: Relevance
“…The results showed that the notifications are resultant from AE that could affect patients, but did not affect. Similarly, another study (22) has demonstrated reports of AE in When asked if there is support from the administration for the implementation of safety management in the institutions, there was unanimous agreement among the NM (Figure 1). the occurrence of errors, mistakes or failures when there was no harm to patients.…”
Section: Discussionmentioning
confidence: 83%
“…The results showed that the notifications are resultant from AE that could affect patients, but did not affect. Similarly, another study (22) has demonstrated reports of AE in When asked if there is support from the administration for the implementation of safety management in the institutions, there was unanimous agreement among the NM (Figure 1). the occurrence of errors, mistakes or failures when there was no harm to patients.…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, another instrument translation and validation study for use in hospitals developed this adaptation. (6) None of the items was excluded from the assessment tool; on the opposite, item 8 was added in section A, suggested by the target population group. The item refers to the access to medical exams as, in the Brazilian reality, the necessary exams are not always offered to the patients freely and in due time.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, subsequent steps need to be pursued, aimed at the operational and measuring equivalence, in order to prove its psychometric properties. (6) The application of a validated questionnaire in studies compared among different contexts in the country and among other countries from different continents will permit understanding the multifaceted phenomenon of safety culture at several Primary Health Care services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,9 Acrescentou-se ao referido instrumento, variáveis que contemplavam a caracterização sociodemográfica e laboral dos participantes O instrumento utilizado contém 42 questões relacionadas à cultura de segurança do paciente, as quais são agrupadas em 12 dimensões. 7 Na busca pelo atendimento integral do objetivo desta investigação, optou-se por analisar as dimensões "Trabalho em equipe no âmbito das unidades hospitalares"; "Abertura para as comunicações"; e "Transferências internas e passagem de plantão", por considerar que estas dimensões melhor retratam a cultura de segurança do paciente na sua interface com o processo de comunicação -objetos de estudo, totalizando 13 itens (questões) de avaliação.…”
Section: Métodounclassified